"I sit all of the time": Health-related time-use among adults with intellectual disabilities. (January 2021) - Powers, Brittany; Patterson, Freda; Palmiere, Katherine; Healy, Sean
Highlights: Formal caregivers were perceived as gatekeepers to, and role-models of, health-related time-use behaviors. The availability and accessibility of spaces to be active determined the health-related time-use composition of adults with ID. Health behaviors (physical activity, sedentary behavior, and sleep) were perceived as being interrelated. The findings support an integrated approach to the promotion of health-related time-use behaviors among adults with ID. Abstract: Background: Adults diagnosed with intellectual disabilities (ID) are more likely to have cardiometabolic risk factors, including low physical activity (PA), high sedentary behavior (SB), and poor sleep. While these behaviors have typically been studied in isolation, emerging frameworks propose a more integrated approach to the study of these behaviors, asserting that the relative proportion of time spent in each of the health-related time-use behaviors (i.e. PA, SB and sleep) across the 24 -h period is a more powerful determinant of the incidence and progression of disease. This approach has yet to be considered for adults with ID. The purpose of this study was to explore how adults with ID and their formal caregivers (i.e. employed caregivers) perceived their health-related time-use, including the factors that influence their time-use. Method: Five focus groups were conducted with twelve adults with ID and ten formal-caregivers. Consistent with an interpretive paradigm, this study employed an interpretative phenomenological analysis (IPA) methodology. Results: Three interrelated themes were identified: (1) Caregivers as gatekeepers to healthy time-use; (2) Places to move; and (3) Daily movement. The themes captured the participants' perspectives of interpersonal and environmental factors that influence health-related time-use, and how these factors were common to engagement in at least on health-related time-use behavior. Conclusions: Interpersonal factors, including caregivers support and modeling-behaviors, and community factors, in the form of local, accessible, affordable spaces to be active, were identified as the most pertinent factors in determining PA, SB and sleep behaviors. Moreover, adults with ID and caregivers perceived health-related time-use behaviors to be interrelated. Further investigation in this area will ultimately inform the development of pilot interventions that support caregivers as gatekeepers and provide access to health-promoting environments to engage adults with ID in healthy levels of PA, SB, and sleep.